2022
DOI: 10.3390/ma15175959
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Experiments on the In Situ Upgrading of Heavy Crude Oil Using Catalytic Aquathermolysis by Acidic Ionic Liquid

Abstract: Heavy and extra heavy oil exploitation has attracted attention in the last few years because of the decline in the production of conventional crude oil. The high viscosity of heavy crude oil is the main challenge that obstructs its extraction. Consequently, catalytic aquathermolysis may be an effective solution to upgrade heavy crude oil to decrease its viscosity in reservoir conditions. In this regard, a series of acidic ionic liquids, 1-butyl-1H-imidazol-3-ium 4-dodecylbenzenesulfonate (IL-4), 1-decyl-1H-imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…During the ILs application, it has been shown that the water dosage influences the viscosity reduction, and their high cost compared with other catalysts is still a challenge in field applications. Nevertheless, it has been reported that ILs present thermal stability, low vapor pressure, and green characteristics. …”
Section: Catalysts and Hydrogen Donorsmentioning
confidence: 99%
“…During the ILs application, it has been shown that the water dosage influences the viscosity reduction, and their high cost compared with other catalysts is still a challenge in field applications. Nevertheless, it has been reported that ILs present thermal stability, low vapor pressure, and green characteristics. …”
Section: Catalysts and Hydrogen Donorsmentioning
confidence: 99%
“…At the water-metal contact, water is replaced by hydrophobic tails, which also repel the electrolyte, and the polar group of the corrosion inhibitor, which has a great affinity for both. The use of organic compounds as corrosion inhibitors for metal surfaces has been well documented 16 20 because they can combine with heteroatoms such O, N, P, and S-bonds. Non-toxic corrosion inhibitors are desperately needed because organic traditional inhibitors have a negative impact on the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…ILs are increasingly being explored for particular advantages in pace, specificity, and yield rather than just as a substitute for organic solvents in a variety of solvent applications today 29 . Many researchers discussed the functionalization of ILs as asphaltene inhibitors and dispersants, where specific functional groups are introduced to the cations and anions 23 , 33 36 . El-Hefnawy et al 37 used hydrophobic ionic liquids based on the alkyl and aryl imidazolium cation and carboxylic asphaltene as anion as asphaltene inhibitors.…”
Section: Introductionmentioning
confidence: 99%